Lietuvos valstybės veikėjai Kraslage 1941–1954 m. (A. Stulginskis, J. Stanišauskis, S. Šilingas, J. Tonkūnas - Kilikevičienė, Giedrė (Genocidas ir rezistencija, 1999)
One of the most important conditions for the consolidation of Lithuania’s sovietisation was the liquidation of the institutions of state governance, and thus of state actors. The fact that not only those who directly held positions of authority, but also those who had long since retired from civil service, were repressed was indicative of the aim of communist parties of the USSR and the USSR to destroy the people who had created the Lithuanian state and who had contributed considerably to it in general, and the elite of the statesmen in particular.